Novel mouse model for evaluating in vivo efficacy of xCT inhibitor - Ryosuke Yoshioka; Yusuke Fujieda; Yamato Suzuki; Osamu Kanno; Asako Nagahira; Tomohiro Honda; Masao Murakawa; Hiroshi Yukiura (Elsevier, 2019)
xCT, a well-known cystine transporter, is reported to be involved in the proliferation of various cells, such as cancer cells, immune cells, and fibroblasts. xCT inhibitor is expected to be a promising drug for cancer or immune diseases. However, there are little studies reporting that xCT inhibitors improve disease progression in vivo. To invent potent xCT inhibitors in vivo, we established a new in vivo model for assessing efficacy of xCT inhibition.dl-propargylglycine (PPG) was administered intraperitoneally to wild-type C57BL/6J mice. Concentration of cystathionine, another substrate of xCT, in the thymus and spleen was measured by LC-MS/MS.PPG increased cystathionine amounts in the thymus and spleen in a dose- and time-dependent manner. At 7 h after PPG administration, the efficacy of erastin, a representative xCT inhibitor, was clearly shown. We synthesized a new compound, Compound A, which had much higher inhibitory effect on xCT than erastin both in vitro and in vivo.We established a mouse model of PPG-induced cystathionine accumulation for assessing xCT inhibition in vivo. By using this model, we discovered that Compound A was approximately 15 times more effective in vivo than erastin. Keywords: xCT, SLC7A11, System xc−, Cystathionine, Erastin